2004
DOI: 10.1016/j.ymthe.2004.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Use of adenovirus protein IX (pIX) to display large polypeptides on the virion—generation of fluorescent virus through the incorporation of pIX-GFP

Abstract: The adenovirus (Ad) protein IX (pIX) is a minor component of the Ad capsid and associates with the hexons that make up the facets of the icosahedron. In this study, we investigated whether a large protein tag could be fused to pIX without compromising the Ad vector itself. As proof-of-principle, we generated a pIX-green fluorescent protein (GFP) fusion protein. We show that a virus encoding the pIX-GFP can be generated and that pIX-GFP fusion protein was incorporated into the Ad capsid as efficiently as native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 30 publications
3
88
0
Order By: Relevance
“…Besides its role as a structural protein, it is a transcriptional activator (Rosa-Calatrava et al, 2001;Sargent et al, 2004a) and reorganizes promyelocytic leukaemia (PML) nuclear bodies (Rosa-Calatrava et al, 2003) (reviewed by Parks, 2005). Protein IX has been extensively studied as a platform to express foreign peptides on the surface of the capsid (Dmitriev et al, 2002;Le et al, 2004;Li et al, 2005;Meulenbroek et al, 2004;Vellinga et al, 2004Vellinga et al, , 2007. Since protein IX has been so well characterized, we selected it as a fusion partner to test whether 2A sequences could be used to express foreign genes in adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its role as a structural protein, it is a transcriptional activator (Rosa-Calatrava et al, 2001;Sargent et al, 2004a) and reorganizes promyelocytic leukaemia (PML) nuclear bodies (Rosa-Calatrava et al, 2003) (reviewed by Parks, 2005). Protein IX has been extensively studied as a platform to express foreign peptides on the surface of the capsid (Dmitriev et al, 2002;Le et al, 2004;Li et al, 2005;Meulenbroek et al, 2004;Vellinga et al, 2004Vellinga et al, , 2007. Since protein IX has been so well characterized, we selected it as a fusion partner to test whether 2A sequences could be used to express foreign genes in adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that pIX can be modified genetically to incorporate large polypeptides into the Ad capsid (38,47,53,85). pIX is a minor capsid protein that stabilizes the hexon on the facets of the capsid (14,23).…”
mentioning
confidence: 99%
“…Of note, the presence of the pIX-eGPF fusion in purified Ad virions did not appreciably decrease virus viability or capsid stability, and has allowed monitoring of Ad localization in vitro and in vivo. 132,133 Further, other Ad vectors harboring complex ligands at the pIX locale have been reported. [134][135][136] As a whole, these studies have established pIX as a highly relevant capsid locale marked by the highest structural compatibility, with diverse targeting and imaging ligands observed to date.…”
Section: Adenovirus Targeting Via Genetic Modification: Other Capsid mentioning
confidence: 99%